Some scandals in gender-based violence and intimate partner violence - Seeletse, Solly Matshonisa (INSPIRA: Indonesian Journal of Psychological Research, 2023)
This study was requested by victims of gender-based violence (GBV) and intimate partner violence (IPV), who wanted their voices to be heard. They were not interested in their identities being revealed, but they only wanted to share their stories to expose some rot by high-profile people. This paper sought to explore the meanings that these victims attach to the experiences of GBV and IPV in cases where perpetrators are well-to-do, highly respected persons occupying positions of authority in recognized establishments. Six (6) IPV victims, selected using the purposive sampling method, participated in the study. They were interviewed, and their text data was analyzed. The results show that some high-status people perpetrate GBV and IPV, covering the known types of IPV and generating two new ones of IPV extending to the victim's family and threats to divorce their victim. The paper recommends monitoring and evaluating high-status people and also bars GBV and IPV perpetrators from practicing in high-profile trades.